Methanogenic diversity in anaerobic bioreactors under extremely high ammonia levels - ÇALLI, BARIŞ; MERTOĞLU, BÜLENT (ELSEVIER SCIENCE INC, 2005)
To evaluate the effects of high free ammonia nitrogen on methanogens, five laboratory scale UASB reactors seeded with different sludges were operated for 450 days. Throughout the experimental period, free ammonia concentration was gradually elevated up to 750 mg/l. Changes in methanogenic population were investigated by using 16S rDNA/rRNA based molecular methods such as denaturing gradient gel electrophoresis (DGGE), fluorescent in situ hybridization (FISH), cloning and DNA sequencing. Generally, in all of the reactors, moderately high COD removal was achieved in the range of 77-96%. However, in three of the reactors, propionate degradation and in one of them, acetate removal was influenced more severely. In no way, neither of the phases was inhibited in reactor 4 (R4), which was seeded with a biomass concentrated from a landfill leachate. On the other hand, as free ammonia level elevated, instead of a community shift, single coccus shaped Methanosarcina cells previously predominant at low free ammonia concentrations turned into stringent multicellular units, in all of the reactors. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: DGGE; FISH; free ammonia; Methanosarcina; propionate; DIGESTION; INHIBITION; REACTORS; WASTE